M-commerce : global experiences and perspectives - Dholakia, Nikhilesh, 1947-; Rask, Morten, 1971-; Dholakia, Ruby Roy (Hershey, PA : Idea Group Pub., 2006)
Based on research and practitioner-generated reports, this book focuses on the emergence and growth of mobile telecommunications and mobile commerce around the world--Provided by publisher
Includes bibliographical references and index
Keywords: Mobile commerce; Telecommunication systems